-5=(2x+1)

Simple and best practice solution for -5=(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5=(2x+1) equation:


Simplifying
-5 = (2x + 1)

Reorder the terms:
-5 = (1 + 2x)

Remove parenthesis around (1 + 2x)
-5 = 1 + 2x

Solving
-5 = 1 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-5 + -2x = 1 + 2x + -2x

Combine like terms: 2x + -2x = 0
-5 + -2x = 1 + 0
-5 + -2x = 1

Add '5' to each side of the equation.
-5 + 5 + -2x = 1 + 5

Combine like terms: -5 + 5 = 0
0 + -2x = 1 + 5
-2x = 1 + 5

Combine like terms: 1 + 5 = 6
-2x = 6

Divide each side by '-2'.
x = -3

Simplifying
x = -3

See similar equations:

| 5x+3=13+4x | | 1/10*2= | | Y=-100+4x^2 | | (x+20)(x)=4800 | | 3v(2v+1)=0 | | 4x^2-20x=-21 | | 8*1/4= | | log(2x-1)=0 | | 1/12*4= | | 1/12*6= | | 66=92/11(88)+b | | 19x-61+3x+1=180 | | 10*1/5= | | (6y-6)+4y+24=81 | | 1/3*3= | | 7x4/11 | | 42=-2(n+6)+m | | 5v+3v=16 | | v=(5X-4)(X+4)(2X-1) | | 4.8+x-5=3.6 | | (2n+7)(6n+7)=0 | | 7/12-4/9= | | (-3x)-9=-27 | | 2x-5(-0.25)=1 | | -5x+9=-4x+1 | | 16=-5+7r+7 | | 8/15÷-4/9= | | log[2](12x)-log[2](5x^2)=6 | | 3t^2-7t-20=10 | | 5(1+8n)=40+5n | | 1/3x3= | | (u-5)(3u-5)=0 |

Equations solver categories